FEATURES OF ACCOUNTING FOR FINANCING AGRICULTURAL PRODUCERS - Y. Andreev (Trakia Journal of Sciences)
Market transformations and developments over the last decade in the Bulgarian economy have mainly affected the financing system for the agrarian sector. The formation and development of financial and credit relations in rural areas has revived the processes of credit cooperation between farmers. The market environment sets out the general rules for the production and exchange of goods and services: it depends on the costing framework and the choice of how they are organized. In essence, agri-industry producers act primarily as consumers of financial and credit institutions, which on the one hand attract temporary free funds to shareholders and other financial institutions; on the other hand, they meet the different financial needs of the members of the farmers with these funds raised. The study of the theoretical and practical features of reporting to farmers in the agrarian sector shows that this is a little studied area. It is mainly in almost complete isolation from the realities of the market economy, which puts new tasks for financial co-operation. The inadequacy of accounting in the agrarian sector is becoming more obvious with the entry of Bulgaria into the European Union and the common agricultural policy.